Maturity parameters characterization and classification of Lemon (Citrus limon (cv. California)) based on reflectance-fluorescence imaging and machine learning model - Firdaus, Yelina Kusuma; Prasetyo, Joko; Hendrawan, Yusuf; Al Riza, Dimas Firmanda (International Journal of Agricultural Technology, 2025)
Reflectance and fluorescence imaging were employed to assess maturity in California lemons (Citrus limon cv. California) based on skin color and texture, alongside internal quality indicators. Fluorescence imaging outperformed reflectance alone in predicting maturity levels, likely due to enhanced capture of biochemical and textural variations in lemon surface. Machine learning analysis using both support vector machines (SVM) and k-nearest neighbors (k-NN) revealed that SVM models trained on fluorescence images provided the most accurate classification. Specifically, fluorescence imaging data processed with SVM (without scaling) achieved 100% accuracy in training and 92% in testing, surpassing other model and feature configurations. These findings showed the utility of fluorescence imaging for potential, non-destructive lemon maturity classification, offering a promising framework for broader applications in citrus and other horticultural commodities.